2019
DOI: 10.1051/e3sconf/201911102050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between attributes of individual workers and concentration at work

Abstract: Working environments are becoming far more diverse. For example, Activity-Based Working (ABW), a new style of working where workers choose their own work environment, is now attracting attention. An office that introduces ABW is comprised of various spaces, including open plan workspaces, corresponding to the ways of working. However, such an office may result in distraction. Therefore, it is necessary to identify the environmental factors that affect individual workers’ concentration at work. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…They also reported that evidence of an association between gender and age on satisfaction scores was limited, in contrast to direct associations with varying personality traits. A further study by Sugino et al (2019) observed that highly agreeable workers tended to be more distracted by the information and communication technology and interior environment in ABW, while extraverts had an inverse correlation with distraction and were less easily distracted.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…They also reported that evidence of an association between gender and age on satisfaction scores was limited, in contrast to direct associations with varying personality traits. A further study by Sugino et al (2019) observed that highly agreeable workers tended to be more distracted by the information and communication technology and interior environment in ABW, while extraverts had an inverse correlation with distraction and were less easily distracted.…”
Section: Resultsmentioning
confidence: 91%
“…Five studies (Wadu Mesthrige and Chiang, 2019; Budie et al , 2019; Sugino et al , 2019; Christersson et al , 2017; Mache et al , 2020) investigated how human-related attributes can affect success of a workspace designed to support ABW. Wadu Mesthrige and Chiang (2019) showed that introverts generally preferred private workspaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable amount of literature has been published on effects of ABW environments on the occupants. Their analysis might be conducted on a sample from one industry sector such as finance (Ekstrand and Damman, 2016), health (de Kok et al , 2016), government (Babapour, 2019), research (Sugino et al , 2019) and consultancy (Wadu Mesthrige and Chiang, 2019), or they might have investigated several industry sectors as one sample (Budie et al , 2019; Wohlers et al , 2017). Either of these study groups has not focused on the industry sector as their mainstream, nor have they looked at satisfaction/dissatisfaction that might raise from the type of industry or a comparison between different industry sectors.…”
Section: Introductionmentioning
confidence: 99%